The effects of conjugated linoleic acid supplementation on inflammatory cytokines and adipokines in adults: A GRADE-assessed systematic review and dose–response meta-analysis - Rastgoo, Samira; Shimi, Ghazaleh; Shiraseb, Farideh; Karbasi, Ashkan; Ashtary-Larky, Damoon; Yousefi, Mohsen; Golalipour, Elnaz; Asbaghi, Omid; Zamani, Mohammad (Frontiers in Immunology, 2023)
Background and Aims: previous studies have reported that conjugated linoleic acid (CLA) supplementation may effects on inflammatory cytokines and adipokines. However, the general impact of CLA supplementation on inflammatory cytokines and adipokines in adults is not fully understood. Methods: randomized controlled trial's (RCTs) examining the effects of CLA supplementation on c-reactive protein (CRP), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), adiponectin and leptin, published up to March 2022, were identified through PubMed, SCOPUS, and ISI web of science databases. 42 studies, including 1109 participants, were included and analyzed using a random-effects model to calculate weighted mean differences (WMDs), with 95% confidence intervals (CI). Results: Findings from 42 studies, with 58 arms, indicated that CLA supplementation significantly decreased IL-6 and TNF-α levels, also, slightly increased CRP levels were observed. However, adiponectin and leptine levels did not change after CLA supplementation. Subgroup analysis demonstrated that CLA supplementation reduced adiponectin and leptin in females. Conclusion: It seems that CLA supplementation slightly affected inflammatory cytokines and adipokines levels in adults.